Analisis laporan keuangan terhadap financial distress pada sektor barang konsumen primer - Asiamufidiawati, Isnaeni Dyah; Handayani, Anita (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The aim of this research is to determine which companies will bear or face the risk of bankruptcy during the Covid-19 pandemic. The aim of this research is to create a more accurate model in predicting financial distress. The subjects of this research were 75 major consumer product industrial manufacturing companies listed on the Indonesia Stock Exchange (BEI) between 2020 and 2022. The Grover, Altman Z-Score, Springate, and Zmijewski methods were used in the analysis. Researchers used quantitative research methods and descriptive analysis. Based on research findings, the Altman Z-Score model which has an accuracy of 29% is the most accurate model of the four models tested in the primary consumer products sector listed on the IDX. The other three models, namely the Springate model, Zmijewski model, and Grover model, each have accuracy levels of 12%, 4%, and 1%. Thus, the Altman Z-Score model can be said to be the most helpful in predicting financial distress in manufacturing companies listed on the Indonesia Stock Exchange in the primary consumer products sector between 2020 and 2022.